Aperture coupled CPW feed for high gain and broadband circularly polarized slot loaded square patch metasurface antenna. Issue 4 (15th February 2022) - Guthi, Srinivas; Damera, Vakula
Abstract: A single layer planar antenna is designed for high gain and broadband circular polarization. The metasurface antenna consists of 3 × 3 arrays of 45° rotated slot‐loaded square patches on one side of the substrate. The stub loaded CPW fed aperture is designed on another side of the substrate to excite the metasurface antenna. Moreover, the size of square patches in the middle row is increased to achieve broadband bandwidth in −10 dB reflection coefficient and 3 dB axial ratio. Furthermore, the size of slots in the middle patches is increased to further enhance the bandwidth of −10 dB reflection coefficient and 3 dB axial ratio. The designed antenna has attained an impedance bandwidth of 30% (4.56–6.21 GHz) with an axial ratio bandwidth of 8.6%(5.23–5.7 GHz). Moreover, the peak value of antenna gain is 10.21 dBi which is incredibly very large in single layer planar antennas. The measured and simulated results are almost close to each other.